2008
DOI: 10.1093/geront/48.supplement_1.36
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Assistants' Job Commitment: Effect of Nursing Home Organizational Factors and Impact on Resident Well-Being

Abstract: The finding that greater job commitment of CNAs is associated with better quality of relationships and life for residents implies that better jobs lead to better care. Culture change transformation that increases CNA autonomy, knowledge input, and teamwork may not increase workers' commitment to jobs without improvements in basic supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 32 publications
5
109
2
1
Order By: Relevance
“…3 Research has demonstrated that when direct care workers' wages are increased, recruitment and retention improve. [23][24][25] However, long-term care employers have a diminished capacity to increase wages and benefits, because more than 70 percent of financing comes from Medicaid and Medicare, which seek to limit costs regardless of labor-market conditions. Compensation for those employed in longterm care is even lower than for licensed professionals caring for older adults in acute and primary care, which has been recognized as inadequate.…”
Section: 35mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Research has demonstrated that when direct care workers' wages are increased, recruitment and retention improve. [23][24][25] However, long-term care employers have a diminished capacity to increase wages and benefits, because more than 70 percent of financing comes from Medicaid and Medicare, which seek to limit costs regardless of labor-market conditions. Compensation for those employed in longterm care is even lower than for licensed professionals caring for older adults in acute and primary care, which has been recognized as inadequate.…”
Section: 35mentioning
confidence: 99%
“…Not surprisingly, licensed practical nurses and direct care workers do not feel that their jobs are respected-a perception that contributes to job dissatisfaction and high turnover rates. 25,27,28 Other workplace challenges include inflexible work flow and job design, ethnic and racial tensions because of the high degree of cultural diversity in long-term care settings, and a paucity of career advancement opportunities. 25,28,29 Principle 2: Recognizing A Distinct Long-Term Care Workforce…”
Section: 35mentioning
confidence: 99%
“…Home health care workers (who have roles similar to that of CNAs, but do not have the formal training) have begun to join fast-food workers in these widespread strikes and the only-slightly-less-marginal CNAs might find inspiration in these kinds of actions. The case for better working conditions for CNAs is bolstered by evidence that nursing home resident well-being is greater where CNA job satisfaction is higher (Bishop et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Second, wages are not the only factor contributing to the high rates of turnover in the nursing homes. A large number of factors are associated with turnover including characteristics of the worker, the nursing home and the environment [174][175][176][177][178][179][180]. In addition, Mukamel found that high turnover was associated with net savings for nursing homes, which may explain the persistence of high turnover over the last decades [181].…”
Section: Hypothesis Testingmentioning
confidence: 99%